National British Orthodontic Society (BOS) Orthognathic Audit 2017–2018. (December 2019) - Ireland, Anthony J; Atack, Nicola E; Cunningham, Susan J; House, Kate; Cobourne, Martyn T; Hunt, Nigel P; Sherriff, Martyn; Sandy, Jonathan R
Objective: To carry out a UK national clinical audit of orthognathic acceptance criteria and information provided to orthognathic patients before treatment. Design: National clinical audit. Setting: Data collected using Bristol Online Surveys. Participants: Sixty-nine UK hospital orthodontic departments submitted data. Methods: Data were collected at two time points using Bristol Online Surveys over a period of 12 months. These were before treatment at the first multidisciplinary clinic (MDT) and immediately after surgery. The data collected included: Index of Orthognathic Functional Treatment Need (IOFTN); Index of Orthodontic Treatment Need (IOTN); age; previous orthodontic treatment; attendance at an MDT; treatment times; and information provision. Results: Eighty-five units agreed to take part in the audit with 69 submitting data, giving a response rate of 81%. The data from 3404 patients were uploaded, 2263 before treatment and 1141 immediately after surgery. Of patients, 91.07% had an IOFTN score of 4 or 5 and 88.73% had an IOTN score of 4 or 5. The mean age at the first MDT was 22 years in the first cohort and 21 years and 4 months in the second immediate post-surgery cohort. Of patients, 37.93% had undergone some form of previous orthodontic treatment, but only 0.28% had undergone previous orthognathic treatment; 96.93% had an MDT confirm that orthodontic treatment by itself was insufficient to adequately correct their functional symptoms. The average treatment time from bond up to surgery was 2 years and 6 months. With respect to information provision, patients received information from a number of sources, principally the British Orthodontic Society (BOS) patient information leaflets and the BOS website Your Jaw Surgery. Conclusions: In the UK, the majority of orthognathic cases fulfil the criteria for acceptance for NHS-funded orthognathic treatment, as outlined by the Chief Dental Officer's interim guidance on orthognathic treatment. This suggests any prior approval process would not be a good use of NHS resources in the commissioning of orthognathic treatment.